Recognition and Prioritization of the Curriculum Ideologies of Medical Science Professors in the Area of the Six Curriculum Components - Faramarz Muhammdipouya; Sohrab Muhammdipouya (Zanjan University of Medical Sciences and Health Services, 2018)
Background & Objective: Identifying the curriculum ideology of professors can serve as a tool and a roadmap for education and curriculum planners. This study aimed to recognize and prioritize the ideology of medical science professors regarding the six curriculum components. Materials and Methods: This descriptive and analytical research was conducted on all professors (N=94) of Baqiyatallah University of Medical Sciences in Tehran, Iran. Data were collected using the questionnaire of curriculum ideology of Schiro. In addition, data analysis was performed in SPSS version 16. Results: In this study, the main priorities of medical science professors regarding curriculum ideology in the six components included the ideology of social construction in goal component, social efficiency ideology in components of teaching, knowledge, and student, and student-centered ideology in learning and evaluation components. Conclusion: While professors considered all curriculum ideologies, they mainly prioritized the social efficiency ideology in all curriculum components. In other words, they mostly emphasized the empowering of students for effective performance.